Missing Web: Reporting a Gap in Fish Predation by Spiders (Arachnida: Araneae) in Indonesia - Muhammad Iqbal; Riza Marlon; Akhmad Junaedi Siregar; Swarlanda (Lembaga Penelitian, Pengabdian Kepada Masyarakat dan Kepustakaan, 2025)
Indonesia, one of the world’s most biodiverse countries, hosts a staggering array of ecosystems and species, many of which remain undocumented, particularly spider (Arachnida: Araneae). While spiders are widely recognized for preying on insects and small animals, fish predation by spiders is a rare behavior predominantly associated with semi-aquatic species such as Dolomedes. This study reports three instances of fish predation by spiders in Indonesia, observed across North Sumatra, Bangka Belitung and East Kalimantan Province during biodiversity fieldwork in 2004, 2022 and 2024. Spider and fish species involved were identified using taxonomic keys and photographic documentation, revealing interactions between Dolomedes sp. and fish from taxa such as Cyprinid, Common Snakehead Channa striata and Licorice Gourami Parosphromenus sp. These findings provide valuable insights into this understudied phenomenon and highlight the need for further research into spider predation in Indonesia’s freshwater habitats.